The Effectiveness of Head of Academic Transformation Leadership and Supervision on Teacher Professionalism Competence - Nadhira Rifqi; Munirul Abidin (Yayasan Avicenna, 2023)
This study aims to analyze the effectiveness of the principal's transformational leadership and academic supervision on teacher professional competence. The research method used is a quantitative approach with a correlational research design. The study population consisted of 61 subject teachers, with a sample of 33 people taken through purposive sampling techniques. The data collection instrument was a questionnaire containing 74 items that had been validated and tested for reliability. Data analysis was carried out using multiple linear regression, t-test, F-test, and coefficient of determination using SPSS. The results showed that transformational leadership had a positive and significant partial effect on teacher professional competence (sig. 0.015 <0.05), while academic supervision had no significant effect (sig. 0.987> 0.05). Simultaneously, both variables had a significant effect on teacher competence with a contribution of 50.3%, while 49.7% was influenced by other factors outside this study. The implications of this study emphasize the importance of strengthening the role of the principal as a transformational leader who does not only focus on administrative aspects, but also as an inspiration and coach for teacher professionalism on an ongoing basis. In addition, these results can be used as a basis for developing principal leadership training programs and improving the quality of academic supervision in educational institutions.